Design of Flat Plate with Equivalent Frame Design Method and Finite Element Method - Sanjaya, Fajar Putra; Bayzoni, Bayzoni; Purwanto, Eddy (Universitas Lampung, 2018)
The flate plate is a thick, evenly solid concrete plate that transfers the load directly to the support column without the aid of a beam or shear head or drop panel. This type of plate can be made quickly because of the formwork and simple reinforcement arrangement. The flate plate is planned to be uniform with dimensions of 5000x4000 mm as many as 9 panels, plate thickness of 150 mm with 25 MPa concrete quality, quality of reinforcement 280 MPa and based on the provisions of SNI 1727; 2013 and SNI 2847; 2013. Flat plate analysis uses the equivalent frame design method, finite element method and SAP 2000 and Microsoft Excel programs. Based of the results of the analysis, the comparison value of moments between the portal method equivalent to SAP 2000 is equal to, whereas between finite element methods and SAP2000 is equal to. In the reinforcement plan, the number and diameter of the reinforcement were obtained in terms of the greatest moment value resulting from the analysis of the equivalent frame design method Keywords: Flat plate, Equivalent Frame Design Method, Finite Element Method